OPTIMALISASI KEDALAMAN TIANG FONDASI BORED PILE DENGAN MENGGUNAKAN SOFTWARE PLAXIS 3D PADA PROYEK PEMBANGUNAN GEDUNG JI’RONAH RUMAH SAKIT AISYIYAH BOJONEGORO - Aldila Oldi Firmansyah; Arik Triarso (Jurnal Vokasi Teknik Sipil, 2026)
Bored pile foundations were used in the Ji’Ronah Building project at Aisyiyah Hospital in Bojonegoro to address soft soil conditions characterised by low bearing capacity and a high potential for settlement. This study aims to calculate the soil’s bearing capacity under the load of the structure above. The results of this foundation optimisation calculation will be compared with the results of analytical calculations using methods previously employed as a benchmark for accuracy, utilising Plaxis 3D software, and compared with field test results. This study utilises SPT data to determine foundation bearing capacity. The method employed is a quantitative case study involving calculations at various depths. The results show the ultimate bearing capacity of a single pile in the calculation using the Luciano Decourt method, namely at a depth of 48 metres: 1,208.19 tonnes; 47 metres: 1,183.12 tonnes; 46 metres: 1,078.60 tonnes; 45 metres: 925.50 tonnes; 44 metres: 810.07 tonnes; 43 metres: 818.18 tonnes; 42 metres: 825.87 tonnes; 41 metres: 849.17 tonnes; 40 metres: 701.16 tonnes. At a depth of 40 metres, the bearing capacity is not met. The conclusion of the Qtk control calculation is 592.798 < V 633.73, which means that a bored pile foundation with a depth of 40 metres and a diameter of 1 metre is not safe for the group’s bearing capacity. Based on the results of the design bearing capacity calculations, the strength of the foundation at Pilecap (P6) was then calculated, comprising 6 bored piles, each 41 metres long and 1 metre wide. The calculation yielded a Pumax value of 1908.03 tonnes and a Pn value of 2980.0 tonnes, indicating that the structure is safe and still meets the required strength capacity. The modelling of the bored pile foundation calculations was carried out using Plaxis 3D software to obtain the ultimate bearing capacity value, calculated as ∑Mstage in kN, resulting in a Qult value of 973.73 tonnes. The difference obtained between the manual analytical (empirical) method of Luciano Decourt and the bearing capacity modelling using the Plaxis 3D software method (numerical) is 14.67%.